Precise Measurement and Compensation of the Micro Product of Inertia for Float Assembly in Pendulous Integrating Gyroscopic Accelerometers - Xiaojun Zhou; Gongliu Yang; Wentao Niu; Yongqiang Tu (Sensors, 2023)
Nonlinear error has become the most critical factor restricting the measurement accuracy of pendulous integrating gyroscopic accelerometers (PIGA) during their improvement. The key to nonlinear error suppression for PIGA is the precise measurement and compensation of the micro product of inertia (MPOI) of the float assembly. However, the existing equipment and procedure for product of inertia (POI) measurement and compensation do not meet the accuracy requirements for MPOI. To solve this problem, novel equipment and procedures are proposed for the measurement and compensation of MPOI. The principle of the proposed measurement method is to simulate the error produced by MPOI in PIGA by using a single-axis turntable to rotate the float assembly along the eccentric axis to generate a centrifugal moment due to MPOI. The principle of the proposed compensation method is to remove the asymmetric mass to reduce the MPOI to zero. Through experimental validation, it is concluded that: (1) the measurement and compensation accuracy of the proposed method are better than 1 × 10−10 kg·m2 and 3 × 10−10 kg·m2, respectively; (2) the proposed method is validated as the MPOI is reduced from 7.3 × 10−9 kg·m2 to 3 × 10−10 kg·m2 for a real float assembly in PIGA, and the quadratic error of PIGA is reduced from 10−5/g0 to 3 × 10−7/g0.